2021
DOI: 10.1507/endocrj.ej20-0519
|View full text |Cite
|
Sign up to set email alerts
|

Independent and interactive associations of season, dietary vitamin D, and vitamin D-related genetic variants with serum 25(OH)D in Korean adults aged 40 years or older

Abstract: Only limited information is available on the inter-relationships between genetic and non-genetic factors such as diet and sunlight exposure with serum 25-hydroxyvitamin D [25(OH)D] concentration. This cross-sectional study aimed to examine the independent and interactive associations of season, dietary vitamin D intake, and SNPs of 11 vitamin D-related candidate genes with serum 25(OH)D concentration among 2,721 adults aged ≥40 years at baseline from the Yangpyeong cohort, a part of the Korean Genome Epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The authors linked the paradoxical rise in serum 25(OH)D concentrations at the start of the COVID-19 pandemic and during the consequent lockdown to the higher proportion of males who were tested while compared to the same period in the previous two years. In general, higher vitamin D concentrations in males than in females have been confirmed in other studies [ 11 , 27 , 30 ], which may indeed offer an explanation for these findings.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The authors linked the paradoxical rise in serum 25(OH)D concentrations at the start of the COVID-19 pandemic and during the consequent lockdown to the higher proportion of males who were tested while compared to the same period in the previous two years. In general, higher vitamin D concentrations in males than in females have been confirmed in other studies [ 11 , 27 , 30 ], which may indeed offer an explanation for these findings.…”
Section: Discussionsupporting
confidence: 77%
“…Similar conclusions have been drawn from other papers published in recent years. Mean serum 25(OH)D concentrations were higher during the summer–autumn seasons compared to the winter–spring seasons [ 12 , 29 , 30 , 31 , 32 ]. The highest prevalence of serum 25(OH)D below 20.0 ng/mL in Greek adults was found in the spring season, precisely in March, by Dimakopoulos et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum 25(OH)D has been reported to vary seasonally [ 20 23 ]. Our study was conducted from May to Nov. Nakamura et al [ 23 ] reported that serum 25(OH)D concentrations in May-Nov were relatively high.…”
Section: Discussionmentioning
confidence: 99%